Strain hardening behaviour of as-quenched and tempered martensite - Wang, LY; Wu, YX; Sun, WW; Brechet, Y; Brassart, LGC; Arlazarov, A; Hutchinson, CR (Elsevier, 2020)
Martensite is a key constituent in advanced high strength steels and plays an important role in providing the high strength. While the strength of martensite has been extensively studied in the past, its low elastic limit and extremely high strain hardening rate remain a puzzle for the steel community. Composite models proposed recently can successfully reproduce these features as result of gradual yielding of microstructural constituents with either variations in intrinsic yield strengths or transformation induced residual stresses. Although these composite models can explain certain observations associated with the deformation of as-quenched martensite, neither can self-consistently describe all the key characteristics in the tension-compression behaviour of as-quenched martensite. Attempts to extend these composite models to tempered martensite have been limited. In this contribution, we conduct a systematic experimental study on the strain hardening of as-quenched and tempered martensite with mechanical testing (e.g. monotonic tension and tension-compression) and interrupted X-ray diffraction. It is shown that the high strain hardening rate, large Bauschinger effect and diffraction line narrowing found in as-quenched martensite during straining can be sustained in tempered martensite tempered up to 400 °C. These phenomena can be understood by considering martensite as a multi-constituent composite having both variations in intrinsic yield strengths and relaxation of transformation induced residual stresses during straining.